Closing Gaps, Increasing Opportunities : A Diagnostic on Women’s Economic Empowerment in Nigeria - World Bank (Washington, DC: World Bank, 2022)
As Nigeria faces the immediate challenge of stimulating economic recovery in the wake of the COVID-19 (coronavirus) pandemic and corresponding economic shocks, it also can address the sizable gender gaps that undermine women’s economic empowerment and hinder inclusive economic growth. Gender disparities in earnings not only hold back the Nigerian economy, they also represent an opportunity: closing the gender gaps in key economic sectors could yield additional gains of US9.3 billion dollars or up to US22.9 billion dollars. Women’s economic empowerment will also be key to accelerating a demographic transition and reaping the gains of a demographic dividend. Drawing on data from the most recent Nigeria General Household Survey (2018-2019), this report makes five critical contributions: (1) highlighting the gender gaps in labor force participation; (2) documenting the magnitude and drivers of the gender gaps in key economic sectors; (3) diving deep into three contextual constraints: land, livestock, and occupational segregation; (4) measuring the costs of the gender gaps; and (5) offering policy and programming recommendations of innovative options to close the gender gaps.